In vitro Melanin Binding of NS-49, a Phenethylamine Class α1A-Adrenoceptor Agonist - Yamada, Tetsuhiro; Okuyama, Yoshio; Mukai, Hideya (Arzneimittelforschung, 2001)
Characteristics of the in vitro binding of NS 49 ((R)-(-) 3’-(2-amino-1- hydroxy-ethyl) 4’ fluoromethanesulfonanilide hydrochloride, CAS 137431-04-0) to syn thetic melanin were determined and com pared with those of other drugs.At all the drug concentrations tested (12.5-200 µmol/l), chloroquine (CAS 54-05-7) had the highest melanin binding (%), followed by ofloxacin (CAS 82419-36-1), NS-49, norephedrine (CAS 154-41-6) and diazepam (CAS 439-14-5). Binding constants (Kb), calculated with the Lang muir adsorption isotherm were, in the or der (largest to smallest) chloroquine, ofloxacin, NS-49, norephedrine, the Kb value for NS-49 being one thriteenth that for chloroquine, one-seventh that for ofloxacin and ten times higher than that for norephedrine.53 % of NS 49 that was bound to syn thetic melanin dissociated during 24 h of incubation after the binding experiment.The percent of dissociation for NS-49 was higher than the values for Chloroquine (5 %) and ofloxacin (39 %). After 1 day incubation in the dissociation experiment, the amount of NS-49 bound per mg of melanin was 23 nmol, being less than the amounts of chloroquine (210 nmol) and ofloxacin (78 nmol).These findings indicate that NS-49 has a lower affinity for synthetic melanin than chloroquine and ofloxacin, which have high affinities and therefore accumulate in melanin containing ocular tissues.
Keywords: (R)-(-)-3’-(2-Amino-1-hydroxyethyl)-4’- fluoromethanesulfonanilide hydrochloride; CAS 137431-04-0; Melanin, synthetic; NS-49, binding to melanin, dissociation from melanin